PERBEDAAN LAJU PERTUMBUHAN KARANG Porites lutea DI PULAU TUNDA - Lalang Lalang; Neviaty P Zamani; Ali Arman (Jurnal Teknologi Perikanan dan Kelautan, 2014)
The skeleton of deposited coral species Porites lutea can provide information to determine the life growth rate of the coral that can be seen on its annual bands. The coral sampling was carried out by using pneumatic drill and then it was analyzed to determine the direction, age, and growth rates of the coral, using X-ray. Result of the research showed that the growth rate of Porites lutea coral in northern station (windward) was in ranged of 0.60 – 2.50 cm/year while the average growth rate was 1.44 cm/year, and in the southern station (leeward) was in ranged of 0.50 – 2.20 cm/year while its average growth rate was 1.21 cm/year. The growth rate of Porites lutea both located north station (winward) and the south station (leeward) showed no significant difference.